SALES CONTRIBUTION THROUGH MOBILE APPLICATION IN CGK-SIN ROUTE AT SINGAPORE AIRLINES LTD JAKARTA - Vica Harahap; Qadria Daeng Malebby; Hendro Kuntohadi (Institut Transportasi dan Logistik Trisakti, 2018)
Passengers show great interest and comfort in using mobile devices to plan and book flights. By launching website and mobile application, Singapore Airlines will become a well-known brand in the society. More people will look for the airlines and use the app which is expected to increase their sales. The purpose of the research is to find out how Singapore Airlines mobile application will impact their ticket sales by doing comparative analysis and analyzing their Compound Annual Growth Rate (CAGR) of total tickets issued before and after they launch the mobile application. CAGR of tickets issued before Singapore Airlines mobile application launched is 0.51%, and 1.16% after they launched the mobile application. From comparative analysis, t-obs as -2.748 and t-table as 2.201 to -2.201 with correlation value 0.45. There is difference between total of ticket issued in Singapore Airlines in Jakarta office for Jakarta – Singapore route before and after Singapore Airlines mobile application launched with moderate level of correlation of mobile application impact to increasing of their ticket sales.